(untitled) (Journal of actual problems of jurisprudence, 2025)
The relevance of writing a scientific article on artificial intelligence lies in the fact that today AI is becoming a key factor in the digital transformation of society, the economy and public administration. Its development requires an analysis of the legal, ethical, and social implications to ensure the safe, responsible and effective use of technology in the interests of both individuals and the state. The purpose of this scientific article is to conduct a legal analysis of the provisions of the Law «On Artificial Intelligence», adopted by the Mazhilis of the Parliament of the Republic of Kazakhstan on September 24, 2025. The analysis of this Law revealed that one of the important aspects of state regulation of social relations in the field of AI – the limitation of artificial intelligence’s influence on human thinking – is not reflected among its stated goals and objectives. This issue concerns the need to establish restrictions on the influence of artificial intelligence on the developing human mind, since the rapid growth of AI capabilities poses a real threat to intellectual development, particularly among the younger generation. In this regard, Kazakhstan needs to take organizational measures to improve public awareness and education on the use of AI systems. Otherwise, the absence of state control over the impact of AI on individual intellectual development may lead to a rapid degradation of Kazakhstani society. This scientific article was prepared as part of the implementation of the grant project «BR27101389 Implementation of Artificial Intelligence Tools in the Lawmaking Process of the Republic of Kazakhstan to Optimize and Improve the Efficiency and Transparency of Legislation», funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan. Keywords: artificial intelligence, legal regulation, lawmaking, thinking, international experience, digital transformation. In this regard, Kazakhstan needs to take organizational measures to improve public awareness and education on the use of AI systems. Otherwise, the absence of state control over the impact of AI on individual intellectual development may lead to a rapid degradation of Kazakhstani society. This scientific article was prepared as part of the implementation of the grant project «BR27101389 Implementation of Artificial Intelligence Tools in the Lawmaking Process of the Republic of Kazakhstan to Optimize and Improve the Efficiency and Transparency of Legislation», funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan. Keywords: artificial intelligence, legal regulation, lawmaking, thinking, international experience, digital transformation.